Matching Aspirations : Skills for Implementing Cambodia's Growth Strategy - World Bank (World Bank, Phnom Penh, 2013)
Over the past decade, Cambodia improved the skills of its workforce at a slower rate than other countries in East Asia. And, although Cambodia's firms do not perceive skills as their main business constraint, skills shortages may negatively affect the process of both industrial and agricultural upgrading and economic diversification. Employers point to a structural imbalance in skills supply, including a relative shortage of vocational training graduates compared to university graduates. This report provides valuable insight for Cambodia to develop the skills necessary to match the country's development aspiration. At the same time, it outlines specific actions to create opportunities for access to information in the skills market, to expand household-oriented interventions, to improve school retention, and to strengthen second-chance options - including technical and vocational education and training. This report further proposes how to expand financing for early childhood development effectively, to strengthen institutions, and to promote incentives toward better results among skills providers, including higher education institutions. The analysis in this report represents an important collaborative contribution to Cambodia's growth strategy and human development agenda.